Preparation and Characterisation of Y3fe5o12-Filled Polyvinylidene Fluoride Composite - Mohd Saad, Mohd Hashim (2007)
This research project was undertaken with the main objective of preparing and characterising a wave absorbing material by utilising a magnetic material with polymer as the base material to provide the carrier template. Polyvinylidene fluoride (PVDF) was chosen as the polymer due to the well-established physical properties. Yttrium iron garnet (YIG) was chosen as the magnetic filler due to its well known microwave absorbing properties. Preparation of YIG particles was carried out via a sol-gel method from nitrates raw material with a citrate route. It was found that with this method employed, the sintering temperature of YIG was minimised to 800ºC compared to 1300ºC for a normal solid state reaction method. PVDF powder was supplied by manufacturer and its film was prepared by dissolving it in cyclopentanone. This method was chosen to reduce the heating cost of preparation as a normal preparation would require hot melting of the PVDF powder. It was found that up to 30 weight percent (wt%) of PVDF could be dissolved in cyclopentanone successfully. Higher wt% hindered total dissolution of PVDF. Dissolution of PVDF powder in cyclopentanone was carried out by magnetic stirring at about 200 RPM for half an hour followed by another half an hour of stirring and heating (200 RPM and 90ºC). The whole process was carried out under reflux condition and the gel formed after the stirring was left to cool down for a few minutes. The gel was cast onto a petri dish to form film. PVDF-YIG composite was prepared by the same PVDF preparation method with additional YIG particles prepared as a raw material component. The composition of YIG is limited to 20 wt%. It was found that YIG particles prepared had an average crystallite size of about 51 nm and YIG single phase was formed at sintering temperature as low as 600ºC. Temperature of 800ºC was chosen as the sintering temperature for preparation of YIG filler particles for the composite due to a better garnet phase formed as observed by XRD. PVDF with 10 wt% of PVDF dissolved in cyclopentanone was chosen for the composite preparation. The PVDF film prepared was found to be highly crystalline with a major XRD peak observed at 77.7º (2θ). This peak was never reported before for PVDF. The PVDF film had leaf-like morphology with observable fibrils. FT-IR results confirmed the YIG and PVDF prepared conformed to reported results. EDX analysis showed that all elements were traceable although with some deviation from theoretical values. Magnetic analysis of YIG, PVDF and PVDF-YIG composites showed that all the samples prepared were wave absorbing. It was found that the PVDF film without any filler was a magnetic material and had a better wave absorbing property than the YIG itself. It was also found that imaginary permeability of composite samples showed a capacitive instead of inductive character. However, the best wave absorber was found to be the composite with 1 wt% of YIG filled which can operate at a frequency range of 2 MHz – 1 GHz with a real permeability of about 200.